Applying Petitmengin's Explicitation Interview Method to Elicit the Lived Experience of Breathing Upon Waking by an Individual With Cystic Fibrosis. (December 2020) - Ladores, Sigrid
Breathing is an act that most people do not consciously evoke unless there is a presence of illness that affects the respiratory system. Adults generally take in 12 to 15 breaths per minute without even a thought about the body's mechanics that allow for proper oxygenation and ventilation. However, for those with pulmonary compromise, breathing becomes a very conscious, deliberate, and sometimes laborious act. The purpose of this paper is to demonstrate the use of the explicitation method by Petitmengin by interviewing a subject to elicit the lived experience of breathing by an individual with end-stage cystic fibrosis (CF). To apply the interview method, the following phenomenological question guided the interviewer's approach: What is the lived experience of breathing upon waking for an individual with CF? This paper includes a transcription of the interview followed by a self-critique, textual analysis, and discussion of the implications to health care.